2013
DOI: 10.1097/adm.0b013e31828e6b21
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine and Medication Management in a Community Corrections Population

Abstract: Acceptability and feasibility of this approach were demonstrated by the ability to enroll and randomize the target sample of participants over 2 weeks with high retention and low rates of adverse events through 1-month follow-up. This pilot study demonstrated that this population could be successfully engaged in treatment and show reductions in risky behaviors. However, more intensive interventions may be needed to reduce opiate use to reach this vulnerable population at their point of contact with the crimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Lind et al (2005) found that for every 100 females under 30yrs on an OST programme for one year there was a reduction of 44 charges overall (with 27 for women over 30 yrs and 10 for men) (p=<0.0001). Less positive results were found by Cropsey et al (2011Cropsey et al ( & 2013. Whilst DUWOs receiving buprenorphine to aid relapse prevention participated in and completed treatment at a significantly higher rate than the placebo group (p=<0.0001); on 3 month follow up there were no difference with 83% of both groups having a positive urine opiate screen.…”
Section: Opiate Substitution Therapymentioning
confidence: 82%
“…Lind et al (2005) found that for every 100 females under 30yrs on an OST programme for one year there was a reduction of 44 charges overall (with 27 for women over 30 yrs and 10 for men) (p=<0.0001). Less positive results were found by Cropsey et al (2011Cropsey et al ( & 2013. Whilst DUWOs receiving buprenorphine to aid relapse prevention participated in and completed treatment at a significantly higher rate than the placebo group (p=<0.0001); on 3 month follow up there were no difference with 83% of both groups having a positive urine opiate screen.…”
Section: Opiate Substitution Therapymentioning
confidence: 82%
“…The feasibility and acceptability of providing buprenorphine treatment at a community corrections site in Alabama was examined by Cropsey and colleagues (2013). This pilot study was conducted with 30 men and women with opioid dependence who were on parole, probation, or drug court supervision.…”
Section: Resultsmentioning
confidence: 99%
“…That study found no difference in illicit opioid or cocaine use, or incarceration over a 6-month post-treatment entry follow-up. The only other reports were longitudinal cohort studies of patients on parole or probation receiving buprenorphine treatment without a comparison group (Cropsey, et al, 2013; Gordon, et al, 2015) that found significant pre-treatment to 3-month follow-up reduction in illicit opioid use and in self-reported criminal behavior (Gordon, et al, 2015) and a significant reduction in drug injection but not in opioid positive urine tests from baseline to short-term follow-up (Cropsey, et al, 2013). These limited data support the use of buprenorphine through drug treatment programs for individuals under community supervision.…”
Section: Resultsmentioning
confidence: 99%
“…We are aware of only three published studies in the US of buprenorphine pharmacotherapy treatment of OUD in community corrections populations. [24][25][26] Moreover, none of these studies systematically examined the impact of co-location of buprenorphine treatment services at the community criminal justice supervision office. However, these studies did demonstrate the feasibility, acceptability, and effectiveness of treating individuals in community supervision with buprenorphine.…”
Section: Buprenorphine Pharmacotherapy With Community Corrections Populationsmentioning
confidence: 99%